Detection and loudness of AM signals for normal and hearing-impaired subjects - GEERS, W.; OZIMEK, E. (Archives of Acoustics, 2014)
The study comprises two experiments pertaining to the perception of sounds with parameters changing in time, by normal-hearing subjects and by hearing-impaired subjects, who had a sloping high-frequency hearing loss originating from a cochlear impairment. The first experiment deals with the determination of the AM detection thresholds, for 3 normal-hearing and 3 cochlear-impaired subjects. In the second experiment, the loudness of AM signals of different parameters, relative to the loudness of a sinusoidal tone was determined by the same group of subjects. Measurements were made for carrier frequencies (f_e) equal to: 250, 500, 1000, 2000 Hz, and for modulation frequencies (f_m) equal to: 4, 8, 64, 128, 256 Hz. It was stated that for low f_m the determined detection thresholds for the normal-hearing subjects were roughly similar to those for the cochlear-impaired subjects. However, for higher f_m the thresholds decrease for the normal-hearing subjects, whereas they tend to increase for the hearing-impaired subjects. Thus, one can assume that for higher f_m, temporal resolution of the auditory system is significantly affected by cochlear hearing loss. As regards the loudness of AM signals, the data showed that for f_m greater than the critical band, the loudness of AM signals increased with f_m for the normal-hearing subjects, whereas it remained independent of f_m for the hearing-impaired subjects.